A atuação do tradutor e intérprete de língua de sinais no processo de ensino - aprendizagem de estudantes surdos em contexto escolar inclusivo: desafios, barreiras e alternativas pedagógicas - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This research came about from my personal quest, as a Translator and Interpreter of Libras (TILS Libras), to understand the importance of this professional, demonstrating the challenges experienced in the school pedagogical context, contributing to the academic scientific production of the Master's Program in Teaching at the Federal University of Pampa. It aimed to reflect on the challenges experienced by professionals who are Sign Language Interpreters Translators in the educational performance with deaf students in the context of inclusive school education, as well as strategies to facilitate the work of these professionals in resolving conflicts experienced in the scope of inclusive education, working in municipal, state, federal and private school spaces in the city of Bagé. I used as a basis the current legislation of inclusion in Brazil, Law No. 13.146/2015, to draw some specific discussions about the challenges to the conduct and daily performance of these professionals in the process of school inclusion of students with deafblindness. I also based myself on theorists who work on issues of deaf education, sign language and the performance of TILS. My overall goal in this research was to point out challenges experienced by professionals through possible strategies to facilitate the work of TILS, as well as assist in resolving the conflicts constantly experienced by these professionals in relation to the performance performed with deaf students in inclusive education. The methodology of this research was based on the Intervention type, from readings and studies of authors such as Quadros (1997), Lacerda (2011), Skliar (1999), Karnopp (1994), among others who also deal with the proposed theme. As research instruments, electronic forms were used, in addition to face-to-face meetings, organized by the methodology of Focus Group, whose research participants were TILS working in the public educational spheres of the municipality of Bagé. Thus, I proposed a reflection on the ethical practice of TILS / Libras in relation to the assumptions of inclusive education, considering the right of full access to communication, information and training of students with deafblindness. In addition, a look was taken at the strategies that the Sign Language Interpreters Translators use to rescue the history of interpretation in Libras in the city of Bagé and the obstacles that they face in the implementation of current legislation, so necessary in the teaching-learning process in inclusive school context - barriers and pedagogical alternatives.
Keywords: Educação de Surdos; Educação Bilíngue; Tradutor e Intérprete de Língua de Sinais; Educação Inclusiva; Acessibilidade pedagógica; Deaf Education; Bilingual Education; Translator and Interpreter of Sign Language; Inclusive Education; Pedagogical accessibility; CNPQ::CIENCIAS SOCIAIS APLICADAS